Health symptoms and post-COVID-19: Comparing symptomatic groups based on self-reported and primary care data - Jenny Gerbecks; C. Joris Yzermans; Michel L. A. Dückers; Mark Bosmans; Christos Baliatsas (PLoS ONE, 2025)
Introduction Health symptoms are common in the general population. Relatively little research has focused on health symptoms in context of the COVID-19 pandemic between people with different manifestations of COVID-19. Aim of this study was to assess symptom differences between individuals suffering from post-COVID-19, individuals infected with COVID-19 but not suffering from lasting symptoms (‘ex-covid’), and non-infected individuals. Methods A 2022 nation-wide cross-sectional health survey was combined with routine primary care data. The response rate for the survey was 32%. The questionnaire data consisted of 315,586 respondents, and the electronic health record (EHR) data included 29,797 patients with merged questionnaire data. Prevalence of individual symptoms and number, duration, and severity of symptoms were analyzed. Results Individuals with post-COVID-19 reported more (IRR 1.48 [CI 1.46–1.49]), longer lasting (1.92 [CI 1.88–1.96]), and more severe symptoms (2.00 [CI 1.96–2.05]) than the ex-covid group. Post-COVID-19 also reported more (1.55 [CI 1.52–1.57]), longer lasting (1.87 [CI 1.82–1.92]), and more severe symptoms (1.95 [CI 1.89–2.01]) compared to non-infected. Ex-covid reported more symptoms than the non-infected, but on average, their symptoms lasted a shorter duration and were experienced as less severe. In EHRs, symptoms between groups showed generally the same pattern. Conclusion & discussion This study points at variation in symptomatology after COVID-19 infection. Individuals with post-COVID-19 experienced more, longer-lasting, and more severe symptoms compared to the other two groups. This study was one of the first to assess group differences between groups with different types of COVID-19 infections.